2018
DOI: 10.1111/bjd.16476
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of omalizumab for the treatment of chronic spontaneous urticaria

Abstract: Omalizumab is cost-effective compared with SoC. The outcomes of this study were used to establish omalizumab as third-line therapy in the Dutch treatment guidelines for CSU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
0
19
1
1
Order By: Relevance
“…The results of that study were used to establish omalizumab as third-line therapy in guidelines for CSU treatment in The Netherlands. 81 A similar outcome was confirmed in a study conducted in the UK which showed that “with a deterministic ICER of £3,183 in the base case, omalizumab was associated with increased costs and benefits relative to SOC”. Further, in that study, the productivity index was one of the main indicators but, even considering early discontinuation in non-responders, the impact on results was not significant.…”
Section: Issues To Be Investigated In Omalizumab Treatmentmentioning
confidence: 61%
“…The results of that study were used to establish omalizumab as third-line therapy in guidelines for CSU treatment in The Netherlands. 81 A similar outcome was confirmed in a study conducted in the UK which showed that “with a deterministic ICER of £3,183 in the base case, omalizumab was associated with increased costs and benefits relative to SOC”. Further, in that study, the productivity index was one of the main indicators but, even considering early discontinuation in non-responders, the impact on results was not significant.…”
Section: Issues To Be Investigated In Omalizumab Treatmentmentioning
confidence: 61%
“…Although already demonstrated in Kanters et al . and other studies, real‐life data could further increase the cost‐effectiveness of omalizumab in CSU. With a very good safety profile, the response rate to omalizumab in real‐life studies seems slightly superior (> 80%) to the clinical trials GLACIAL and ASTERIA that were used for incremental cost‐effectiveness ratio calculations .…”
mentioning
confidence: 90%
“…This issue of the BJD includes an interesting study showing that omalizumab as an add‐on to standard of care (up to fourfold the licensed dose of H 1 ‐antihistamines) is a cost‐effective treatment for chronic spontaneous urticaria (CSU) in the Netherlands . This has previously been shown in the U.K., and in other countries, even considering local particularities of health systems and local recommendations for using omalizumab for CSU .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, studies have established a clear advantage in the cost-effectiveness for omalizumab compared with cyclosporine in the management of CU. 7 Further, the safety profile of cyclosporine in children vs omalizumab is not negligible. Cyclosporine use is associated with increased risk for decreased renal function and hypertension in a dose-dependent manner.…”
mentioning
confidence: 99%